2011
DOI: 10.4238/2011.december.19.5
|View full text |Cite
|
Sign up to set email alerts
|

Sulcus vocalis: evidence for autosomal dominant inheritance

Abstract: ABSTRACT. We found evidence of autosomal dominant hereditary transmission of sulcus vocalis. Four dysphonic patients from three generations of the same family were submitted to videolaryngoscopic examination (three patients) and to direct laryngoscopy (one patient) to diagnose the hoarseness. Sulcus vocalis was diagnosed in all four patients. The finding of four affected individuals in three generations, with vertical transmission affecting man and women, is more consistent with autosomal dominant inheritance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…No recent studies have confirmed this statement, and to our knowledge no other study has investigated the correlation between SV and origin. Other investigators have shown evidence for autosomal dominant inheritance and probable genetic etiology, which could support the thesis of SV as a congenital disorder [26, 27]. …”
Section: Discussionmentioning
confidence: 79%
“…No recent studies have confirmed this statement, and to our knowledge no other study has investigated the correlation between SV and origin. Other investigators have shown evidence for autosomal dominant inheritance and probable genetic etiology, which could support the thesis of SV as a congenital disorder [26, 27]. …”
Section: Discussionmentioning
confidence: 79%
“…Numerous studies have noted type II lesions within the same family members and they are commonly believed to be hereditary in origin. [17][18][19][20][21] Further evidence of congenital sulci was noted in excised neonatal larynges. 22 Silva et al examined 56 larynges for evidence of congenital anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Years to come will demonstrate the advances in medical and tissue engineering in developing tools to restore the microanatomy and molecular biology in sulcus vocalis. Important breakthroughs have already been made and new studies are showing promising results [46,[61][62][63][64][65][66][67], however, further research is required until a standard technique to address sulcus vocalis is found, ending the ancient struggle of the vocal fold to freely vibrate.…”
Section: Futurementioning
confidence: 99%